The Effects of CEO Founder Status and Stock Ownership on Entrepreneurial Orientation in Small Firms. (7th March 2016) - Deb, Palash; Wiklund, Johan
Abstract : This paper studies how governance drives entrepreneurial orientation (EO) in small firms. We argue that founder status and ownership create powerful personal incentives for small firm CEOs to engage in behaviors that influence EO. Integrating stewardship theory and the principal‐principal branch of agency theory, we test our hypotheses on a sample of 339 Swedish firms, and find that CEO founder status is significantly and positively associated with EO, while CEO stock ownership significantly but negatively predicts EO. We additionally test two boundary conditions that show that the founder‐CEO's prior managerial experience in start‐up firms positively moderates the founder‐EO relationship, while contrary to expectations, CEO ownership diversification has no effect on the negative association between ownership and EO. Thus, our study adopts a corporate governance perspective to explain how variations in EO across small firms are driven by the goals and motivations of its leader. Our research also shows that in small, private firms the balance of power is tipped in favor of the CEO rather than the board of directors. Finally, we underline the importance of adopting alternative theoretical lens like stewardship and principal‐principal agency, given that traditional principal‐agent problems are largely mitigated in the small firm context.